Between Architecture, Story, and Place Identity: A Narrative Approach for Creative Placemaking in Museum Design - Aguspriyanti, Carissa Dinar; Benny, Benny; Christine, Venita; Fernando, Delvin; Tan, Angelina (Itenas, Institut Teknologi Nasional Bandung, 2023)
Museum architecture is required to tell a story more than just the physical building to be able to convey the knowledge and messages it carries. When architecture can be enjoyed physically and psychologically, architecture can be more memorable, easier to understand and appreciated by its users. How people value a place can be influenced by a narrative that gives character or identity to that place. Therefore, stories play a crucial role in making a place and shaping its identity. Placemaking concept has several types of approaches to transform spaces and enhance their significance. In particular, this study explored how to use narratives for creative placemaking in museum design, using a qualitative descriptive method that refers to the design process. Using narratives in architectural design has been well-known as storytelling architecture involving two techniques that are ‘storytelling as a metaphor’ and ‘storytelling through sequencing’. The results indicated that these techniques play a part in creative placemaking application which has three design principles, particularly in museum design. By incorporating storytelling techniques, architects and designers can create spaces that evoke emotions, foster connections, and enhance the overall experience of a place.